EOQ Optimization Revolutionizes Inventory Management, Delivering Cost Savings Globally: Optimalisasi EOQ Merevolusi Manajemen Inventaris, Menghasilkan Penghematan Biaya Secara Global - Wardhani, Devira Kusuma; Sukmono, Tedjo (Universitas Muhammadiyah Sidoarjo, 2024)
Efficient inventory management is crucial for companies to minimize costs while ensuring adequate supply to meet demand. PT Samawa Tirta Alam, a bottled sweet drinking water company, faces significant inventory management issues, notably with refined sugar raw materials. High transportation costs and fluctuating demand contribute to excessive inventory accumulation and increased storage costs, necessitating an optimization strategy. This study implements the Economic Order Quantity (EOQ) method to address these challenges. Through a mixed-method approach, qualitative data were gathered via observations and interviews, while quantitative analysis utilized historical data to calculate optimal order quantities, frequencies, safety stock levels, and reorder points. Results demonstrate substantial cost savings, with optimal order quantities determined, reducing order frequencies from 12 to 2 times per year, and minimizing safety stock levels. The findings underscore the effectiveness of the EOQ method in enhancing cost-effectiveness and operational performance in raw material inventory management for similar companies. Highlights: 1. Cost Efficiency: EOQ method reduces total inventory costs effectively.2. Operational Precision: Minimizing safety stock enhances operational efficiency.3. Strategic Insight: Integrated approach provides practical solutions for inventory management challenges. Keywords: Inventory Management, Economic Order Quantity (EOQ), Cost Optimization, Raw Materials, Transportation Costs